Effect of Platelet-Rich Fibrin on Composite Graft of Autogenous Bone and Deproteinized Bovine Bone in New Bone Formation in Rabbit Calvarial Defect - Kingkaew Phurisat (Prince of Songkla University, 2011)
Thesis (M.Sc., Oreal Health Sciences)--Prince of Songkla University, 2008